Peran Fintech Dalam Meningkatkan Inklusi Keuangan Syariah Pada UMKM Di Kota Makassar: (Studi Kasus Pada Aplikasi Paytren) - Ramadhan, Fuad (MADINAH, 2021)
This article focuses on examining the role of fintech in increasing Islamic financial inclusion in MSMEs in Makassar City. Based on the results of the study it can be concluded that online payment/transaction methods for Android applications such as Paytren using barcode scans provide several benefits such as convenience and time efficiency so that the transaction process with customers uses less time so that it provides benefits to MSMEs in Makassar City. As well as security in transactions, it is also very secure. With this, it can increase Islamic financial inclusion in MSMEs in Makassar City.